Effect of a single dose of caffeine in pregnant sows on farrowing behaviour, colostrum composition, piglet vitality and growth (Revista de Ciências Agroveterinárias, 2025)
Caffeine is an alkaloid that reduces perinatal hypoxia by acting on adenosine receptors in respiratory centres, enhancing respiratory capacity and piglet viability. This study aimed to evaluate the effects of acute subcutaneous caffeine administration during late gestation in multiparous sows on farrowing, pain behaviours, colostrum composition, and piglet behaviour during lactation. Sows were randomly assigned to two groups: control (NaCl 0.9%) or caffeine (0.5 g/sow/predicted piglet), with treatments given one day before farrowing. No significant effects were observed on farrowing duration, litter size, live or stillborn piglets, or painful behaviour. Although caffeine did not affect birth weight, piglets from the caffeine group gained 0.92 kg more (p
Keywords: methylxanthines; neonatal vitality; farrowing pain; preweaning mortality